Análise numérico-experimental de vibrações induzidas pelo caminhar humano sobre pisos mistos (aço-concreto) - Bárbara Elisa Ferreira (2020)
Over the past few years, problems related to the excessive vibration of composite steel and concrete structures have occurred more frequently in spaces intended for human activities. This fact can be associated with a smaller amount of materials use due to the greater resistance attributed to them, resulting in more flexible structures, slender and with lower natural frequencies, close to the excitation frequencies caused by human activities. With this in mind, the present work aimed to evaluate experimentally and numerically the dynamic behaviour of composite floors (steel-concrete), from a human comfort point of view, when submitted to human walking. The structural model investigated was a real floor system (steel-concrete) under construction, with a total area of approximately 1300 m². A preliminary numerical model was developed to guide the excitation and instrumentation ideal positioning to be adopted in the on-site experimental test. Forthwith, free vibration tests were carried out, to obtain the structure modal parameters, and more than 180 forced vibration tests, with excitation caused by a person walking at different step frequencies and directions. The results indicated values of peak accelerations, coming from one person walking on the floors, below the limit value recommended by standards and design guides, thus being the structure in accordance with the human comfort criteria. Subsequently, an influence analysis of the number of people on the floor’s dynamic response was carried out, where it was noticed that the increase in the number of users walking on the floor also increases the value of peak acceleration. This fact emphasizes the need to carry out experimental evaluations considering the variation in the number of people exercising an activity on the floor, in order to represent in a more real way the vibrations induced in service situations of the structure.